Dialysate sodium concentration: The forgotten salt shaker. Issue 6 (21st October 2018) - Hanafusa, Norio; Tsuchiya, Ken; Nitta, Kosaku
Abstract: The concentration of sodium in dialysis fluid, a major determinant of extracellular fluid volume and blood pressure, plays a major role in the sodium balance in end‐stage renal disease patients. A low dialysate sodium concentration (DNa) reduces interdialytic weight gain (IDWG) and blood pressure and might help ameliorate endothelial dysfunction and inflammation. However, low DNa can also increase the incidence of hypotensive episodes and muscle cramps. Sodium profiling, as typically prescribed in which the DNa is ramped up from above 140 mEq/L to nonphysiological levels, might reduce hypotension in patients with hemodynamic instability but at the cost of the consequences of hypernatremia. Serum sodium concentrations of individual patients fall within a narrow range around a "sodium setpoint." The sodium gradient, the difference between the sodium set point and the DNa, is associated more robustly with clinical outcomes than DNa itself. Sodium concentration presents several issues: the influence of the net negative charge of plasma proteins on sodium flux across the dialysis membrane (Donnan equilibrium); and the clinically important problems in measuring sodium levels. This article presents a review of the clinical effects of DNa and of basic aspects of sodium balance in hemodialysis patients.